PERMEABILITY ENHANCEMENT OF A BCS CLASS III DRUG THROUGH LIPID-BASED NANOPARTICLES: A QUALITY BY DESIGN APPROACH - BHAVANI, MUGGU SANKARA; RAVINDRAN, SARAVANAN (International Journal of Applied Pharmaceutics, 2025)
Objective: Metformin belongs to class III of biopharmaceutical classification. Low bioavailability of 50 – 60% due to its poor permeability and high dose of 500-1000 mg are challenging to the dosage form development of Metformin. Hence, this work was planned to augment the permeability of Metformin so as to improve its oral bioavailability. Methods: Metformin-loaded nanoparticles with lipids, surfactants and bile salts were prepared through double emulsion solvent evaporation technique. Quality by design approach was employed to optimize and develop the nanoparticles. The central composite design was adopted to design the experiment to prepare nanoparticles from several combinations at different concentrations of the lipids and surfactants. These nanoparticles were characterized for yield, entrapment efficiency, solubility and permeability. Impacts of the factors on the solubility change and permeability change were studied by design of experiments analysis. Results: The nanoparticles from the optimized formulation were found to have a size of 262.1 nm with a polydispersity index of 0.352 after design of experiments analysis with statistical significance measured at p<0.05. Importantly, these optimized nanoparticles exhibited permeability of 2.137x10-5 cm/sec, which was 5-times higher when compared to pure Metformin. Conclusion: These results concluded that the oral bioavailability would be improved through improved permeability from the lipid-based nanoparticles of Metformin.